Dynamic relationship between real export, real import, real exchange rate, labor force and real gross domestic product in Malaysia - Emilda Hashim (Tanjong Malim, 2019)
Dynamic relationship between real export, real import, real exchange rate, labor force and real gross domestic product in Malaysia by Emilda Hashim